2016
DOI: 10.1016/j.gore.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Renal transplantation-related risk factors for the development of uterine adenomatoid tumors

Abstract: HighlightsWe analyzed the epidemiological factors for clinical manifestations of uterine adenomatoid tumors.Renal transplantation with immunosuppression therapy is risk factor for the development of uterine adenomatoid tumors.The length of time on dialysis is risk factor for the development of uterine adenomatoid tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…Of note is a growing number of case reports documenting an association of adenomatoid tumors arising in patients who are immunosuppressed for treatment of autoimmune disease or following allograft organ transplantation, and rare examples of immunosuppressed patients with giant or multiple adenomatoid tumors have also been reported. 7 11 This suggests a potential link between adenomatoid tumors and deregulated cytokine signaling pathways within mesothelial cells. Herein, we report the discovery of a defining genetic cause of adenomatoid tumors that may help to explain this association of adenomatoid tumors with immune dysregulation.…”
Section: Introductionmentioning
confidence: 99%
“…Of note is a growing number of case reports documenting an association of adenomatoid tumors arising in patients who are immunosuppressed for treatment of autoimmune disease or following allograft organ transplantation, and rare examples of immunosuppressed patients with giant or multiple adenomatoid tumors have also been reported. 7 11 This suggests a potential link between adenomatoid tumors and deregulated cytokine signaling pathways within mesothelial cells. Herein, we report the discovery of a defining genetic cause of adenomatoid tumors that may help to explain this association of adenomatoid tumors with immune dysregulation.…”
Section: Introductionmentioning
confidence: 99%
“…Specific immunosuppressive agents may affect the pathobiology of AT. PSL, which was administered to all the immunosuppressed AT patients in our series and those in previous reports, could be a candidate. However, PSL is the most commonly used immunosuppressive agent, and it might just be a confounding factor.…”
Section: Discussionmentioning
confidence: 67%
“…Of note, multifocal AT was also identified in non-immunosuppressed patients. Recently, Mizutani et al 19 examined 1094 hysterectomy specimens and identified ATs in 10 of 14 (71.4%) renal transplant recipients who were under immunosuppressive therapy. These authors reported a significant correlation between the occurrence of AT and the length of time on dialysis (P = 0.047).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations